¿El valor de algunos servicios ecosistémicos de los Andes colombianos?: transferencia de beneficios por meta - análisis - Ruiz, Cesar Augusto; Conservation International Foundation (2014)
The economic valuation of biodiversity and ecosystem services plays an important role in Colombia’s conservation planning and economic development, but gathering data to conduct an original study can be expensive. To this end, there is an alternative yet controversial method called "benefits transfer". Here, we present a meta-analysis of available literature on the economic valuation of the Colombian Andes using two approaches: transfer functions and transfer of mean values. The economic value of ecosystem services, which included water availability, recreation and conservation for the Colombian Andes, yielded values between 106 and 339 trillion 2011 USD. However, determining the overall value of ecosystems presents a complex challenge due to the difficulty in the synthesis of the studies, their variability, and the nonexistence of documented experiences. Economic valuation in Colombia is faced with issues in the presentation, collection and variability of data. We concluded that the existing information is insufficient; there are few well-designed studies to procure consistent ecosystem values to support the creation of development policies in Colombia.